1974
DOI: 10.1159/000114604
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of ECT on the Cerebral Circulation in Man

Abstract: The acute cerebral haemodynamic effects of modified ECT were monitored by electrical impedance piethysmography in four patients with schizophrenia and three with depression. A total of 20 recordings were made on these patients; of these, 19 involved the following segments, in sequence: a rest period of 25–115 min, a short period in which Atropine, Brietal, and succinylcholine were given by injection, administration of the ECT, monitoring of post-ECT effects for 10 min, and, finally, a recovery period of up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…REG signals processing is typically based on the analysis of the geometry of the pulse waves, by means of detecting local maximums and minimums as well as other features extracted from the time series [ 57 , 58 ]. In order to determine if the entropy metrics herein proposed outperform this classical analysis, the following set of features were extracted from the recordings: Maximum amplitude (Max) Minimum amplitude (Min) Amplitude range (Range) Slope of the increasing edge (α) Area under the curve of each cardiac cycle (Area) Time between two consecutive maximums (Δtmax) Time between two consecutive minimums (Δtmin) Time between a minimum and its consecutive maximum (Δtmin-max) …”
Section: Methodsmentioning
confidence: 99%
“…REG signals processing is typically based on the analysis of the geometry of the pulse waves, by means of detecting local maximums and minimums as well as other features extracted from the time series [ 57 , 58 ]. In order to determine if the entropy metrics herein proposed outperform this classical analysis, the following set of features were extracted from the recordings: Maximum amplitude (Max) Minimum amplitude (Min) Amplitude range (Range) Slope of the increasing edge (α) Area under the curve of each cardiac cycle (Area) Time between two consecutive maximums (Δtmax) Time between two consecutive minimums (Δtmin) Time between a minimum and its consecutive maximum (Δtmin-max) …”
Section: Methodsmentioning
confidence: 99%
“…These parameters are listed in figure 1. Details of the computer programmes have been published (9,10). Statistical analy sis of the print-out results was undertaken by the university computer centre's IBM 370/ 165.…”
Section: Methodsmentioning
confidence: 99%
“…Very recently we published the immediate results of monitoring ECT by a non-invasive technique of cerebral electrical impedance plethysmography (rheoencephalography, REG) (10). Using computer programmes for the analysis of the REG results it was found for a total of 20 recordings from 7 psychiatric patients that a surging increase in CBF occurred immediately following a single ECT.…”
Section: Introductionmentioning
confidence: 99%
“…The Impedance Plethysmograph (IPG) measures electrical impedance signal changes that vary with the blood content of the segment during each pulse. 2,16,17 Previous research studies 13,16,[17][18][19][20][21][22] have shown the IPG technique to be both reliable and reproducible for use in the quantification of peripheral blood flow.…”
Section: Venous Occlusion Plethysmography (Vop)mentioning
confidence: 99%
“…19 The parameters calculated by the RheoSys program are based upon parameters established in previous studies. [20][21][22][23][24][25][26][27][28][29][30] An appendix detailing this technology and defining the terms used in the in the rest of this article is included.…”
Section: Data Collection Proceduresmentioning
confidence: 99%